Peers and the gender wage gap - Guerreiro, Diogo José Da Costa (2020)
This study investigates the importance of peer effects in the Portuguese economy, as wellas their impact on the gender wage gap. Peer effects are measured using the average of theco-workers fixed effects. While also accounting for individual heterogeneity and firm andjob-title sorting, the results show evidence of positive peer effects on wages (of 4.83% froman increment of one standard deviation in peers’ ”quality”), while 5% of the existent gen-der wage gap can be justified by differences in peer effects. Allowing for heterogeneity inpeers’ spillovers reveals how female workers are more susceptible to spillovers from theirfemale peers in spite of also being more exposed to them due to market segregation.